The Challenges Of Using Google Translate in Translating Written Works Among Third Semester English Study Program Students - Giovani Dwi Yana; Keysia; Oxtapianus Tawarik; Tuminah (Institut of Shanti Bhuana, 2025)
The author chose this topic because Google Translate is a tool commonly used by students, but it still has limitations in accuracy and understanding of context. Many students rely on this tool without adequate evaluation skills for the translation results and their academic quality. By understanding the existing challenges, this study can provide recommendations for students and teachers to improve the effectiveness of using Google Translate in translation learning. This study identifies and analyzes third-semester students' challenges in using Google Translate. The research method used is a qualitative approach with data collection techniques through interviews and questionnaires. The data obtained were analyzed using thematic analysis methods to find patterns and main obstacles faced by students. The results of the study show that students experience various challenges, such as translation inaccuracy, lack of understanding of context, and difficulty in translating technical and academic terms. In addition, dependence on Google Translate also has an impact on students' ability to develop translation skills independently. The contribution of this study in the field of translation is to provide insight into the limitations of Google Translate and suggest strategies to improve the effectiveness of its use in academic contexts. These findings can be the basis for developing a better curriculum for students to learn translation.